A Study on Prevalence of Acute Respiratory Tract Infections (ARI) In Under Five Children in Urban and Rural Communities of Ahmedabad District, Gujarat - Bipin Prajapati; Nitiben Talsania; K N Sonaliya (Medsci Publications, 2011)
Background: Acute respiratory tract infection is a major cause of morbidity and mortality in developing and also developed countries. About 13 million under 5 children dies every year in the world, 95% of them in developing countries, one third of total deaths are due to ARI. Objective: To find out prevalence of ARI in under 5 children living in urban and rural areas of Ahmedabad district Materials and Methods: A cross sectional study was covering 500 under 5 children living in urban (five zone) and rural (five PHC of Sanand taluka) area of Ahmedabad district from September 2008 to March 2009. Results: Prevalence of ARI was found to be 22%, it was higher   in low social class (III, IV and V) (26.56%), Illiterate mothers (24.4%) and primary (23.9%) mothers, Overcrowded houses (28.5%). Conclusion: Prevalence of ARI was lower in urban area (17.2%) as compare to rural area (26.8%) (Combine is 22%). In rural area, it is more because of lack of availability of basic health services, lack of awareness, and other associated factors like overcrowding, low socio-economic status, absence of cross ventilation, indoor air pollution are responsible factors.